EFEK TEACHING GAMES FOR UNDERSTANDING MODEL TERHADAP RESPONSIBILITY ANAK SEKOLAH DASAR - Sri Santoso Sabarini (PHEDHERAL, 2019)
The purpose of this research are: (1). To find out whether there is an influence "Teaching Games for Understanding Models" in physical Education on the character of the responsibility of fourth grade elementary school students. (2). To find out how much influence the "Teaching Games for Understanding Model" at physical education learning on understanding the Responsibility Attitude of fourth grade children in elementary school. This type of research uses the quasi experiment method in the form of pretest-posttes non equivalent control-group design.The research subjects used in this study were fourth grade students of Klumprit 3 Mojolaban Elementary School. Sukoharjo The size of the study subjects was 27 students. The technique of collecting data is using questionnaire responsibility that has been developed from Don Hellison (1995) through a valid and reliable question instrument with Cronbach's Alpha: 0.921. The data analysis technique used in this study used the Wilcoxon difference test to see the gain score of the pretest and posttest. The results of data analysis can be concluded that: (1). There is a significant effect between the Application of the TGfU Learning Model to the Responsibility of 4th grade elementary school students. It is obtained that the calculated Z value for the TGfU Learning Model is -4,543 with a significance value of 0,000 because the significance value is lower than 0.05, the null hypothesis number is rejected, from the research conducted, the hypothesis is accepted. (2).From the description of the data it was seen that the average pre test results of 50.9630 and post tets were 67.4815, thus there was an increase in the influence of the application of the TGfU model on student Responsibility by 16, 52.